WAGES OF INEQUALITY: CORRUPTION AND ECONOMIC HARDSHIP IN SOKOTO STATE - Abdulahi , Musa Hassan (Ayden International Journal of Law, Political Science, and Administration, 2025)
Corruption remains a formidable obstacle to political, economic, and social progress across various political systems, exerting detrimental effects on development efforts and bureaucratic efficiency while eroding the credibility of governmental institutions. In the civil service sector, corruption is particularly pervasive, exerting profound impacts on the provision of public goods and services and hindering socio-economic development in affected states. This article explores the multifaceted nature of corruption within the civil service, highlighting its detrimental consequences such as the abuse of public power for private gain. Such corrupt practices directly contribute to exacerbating poverty levels and impeding economic growth and democratic transitions. Drawing on the works of scholars like Chetwynd et al. (2003) and Adam (2015), corruption in the civil service is delineated as the illicit manipulation of delegated authority, wherein civil servants exploit their entrusted roles for personal benefit. Understanding the intricate dynamics of corruption within the civil service is crucial for developing effective strategies to combat this pervasive phenomenon and foster sustainable development and governance.